2015
DOI: 10.1080/10426914.2015.1048462
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Optimization of Machining Nimonic C-263 Superalloy using Multicut Strategy in WEDM

Abstract: In recent years, Wire-Electrical Discharge Machining (WEDM) has gained popularity in industry due to its capability to generate complicated shapes in exotic materials, irrespective of their hardness. Conventional machining of Nimonic C-263 super alloy is an extremely difficult and costly process due to its high hardness and tool wear rate. The present research work investigates the influence of the WEDM process parameters on different performance measures during machining of Nimonic C-263 super alloy.Mathemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 19 publications
1
36
0
Order By: Relevance
“…In this method, the translation of each response is carried out on a common scale. The desirability function ranges from 0 to 1 [30]. Therefore, the response feedback 'xi' is translated In this experiment, desirability is to get the maximum hardness and minimum wear of the coating.…”
Section: Desirability Testmentioning
confidence: 99%
“…In this method, the translation of each response is carried out on a common scale. The desirability function ranges from 0 to 1 [30]. Therefore, the response feedback 'xi' is translated In this experiment, desirability is to get the maximum hardness and minimum wear of the coating.…”
Section: Desirability Testmentioning
confidence: 99%
“…In a study of Ti6Al4V alloy cut with WEDM; when the values of Ton, Toff, I, Va, fw and tw increase, the cutting width is increased and also the increment of Ton, Va, water pressure and fw increase the MRR is declared [11]. In a study in which statistical analysis and experimental studies were evaluated together, it was emphasized that the most effective parameters on MRR and Ra are discharge current and T on [12][13][14][15][16]. The thermophysical properties of the workpiece, plays a important role in affecting the EDM process.…”
Section: Introductionmentioning
confidence: 99%
“…Mandal et al [12] have used the Response surface methodology (RSM) for optimization of machining parameters in wire electric-discharge machining of Nimonic C-263 superalloy. They have found that the cutting rate is significantly influenced by pulse on time, pulse off time and servo reference voltage.…”
Section: Introductionmentioning
confidence: 99%